SISTEM BANTU KELAYAKAN KAPAL FERRY DALAM PELAYARAN - Qammardin, Qammardin (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
This study aims to analyze the factors that the ships eligibility in making the voyage to avoid the occurrence of marine accidents that are fatal because it is not worthy to ship in the voyage and finish it by using a decision-making system approach. This auxiliary system serves to record the ships eligible ship physical and administrative results prior to the voyage. The auxiliary system in this study was built within the optimization framework designed to solve the ships eligibility issues in making the voyage. The test of ships eligibility in making good and optimal shipping to avoid fatal accidents is not possible without using a good and real-time data management system. With the auxiliary system, data processing and feasibility parameters become faster and produce decisions with a high degree of accuracy. Through this research, we are able to improve the quality of ships eligibility in shipping well in strategic and operational aspects. The research was conducted by using survey method, model development and decision making advisory system. Expected results are in the form of prototype and a vessel assistive aerial system in carrying out a cruise that can be implemented to overcome and reduce the number of marine accidents in the voyage.